RIPK3‐Mediated Necroptosis Regulates Cardiac Allograft Rejection. Issue 8 (1st July 2014) - Pavlosky, A.; Lau, A.; Su, Y.; Lian, D.; Huang, X.; Yin, Z.; Haig, A.; Jevnikar, A. M.; Zhang, Z.‐X.
<x xml:space="preserve">Abstract</x> Cell death results in tissue damage and ultimately donor graft rejection and can occur as an active molecular process through apoptotic, necrotic and newly identified receptor interacting protein 1 and 3 kinase (RIPK1/3)‐mediated necroptotic pathways. Necroptosis leads to the release of inflammatory molecules which can activate host immune cells. This pathway has yet to be studied in heart transplantation. We have found that necroptosis was induced in murine cardiac microvascular endothelial cell (MVEC) under anti‐apoptotic condition following tumor necrosis factor alpha treatment. Necroptotic cell death and release of the danger molecule high mobility group box 1 (HMGB1) were inhibited by the RIPK1 inhibiting molecule necrostatin‐1 and by genetic deletion of RIPK3. In addition, tissue necrosis, release of HMGB1 and graft cell infiltrate were attenuated in RIPK3 null heart allografts following transplantation. Finally, a brief sirolimus treatment markedly prolonged RIPK3 null cardiac allograft survival in allogeneic BALB/c recipients as compared to WT C57BL/6 donor grafts (95 ± 5.8 vs. 24 ± 2.6 days, p < 0.05). This study has demonstrated that RIPK1/3 contributes to MVEC death and cardiac allograft survival through necroptotic death and the release of danger molecules. Our results suggest that targeting RIPK‐mediated necroptosis may be an important therapeutic strategy in transplantation.